The illustrated guide to locomotives of the world a comprehensive history of locomotive technology from the 1950s to the present day, shown in over 300 photographs - Garratt, Colin 1940- (Southwater, 2000)
This pictorial encyclopedia features some of the most influential, famous, and beautifully designed trains from across the world.